Presinapticeskoe tormozenie alpha-motonejronov spinnogo mozga u sportsmenov adaptacionnych k dvigatel'noj dejatel'nosti raznoj napravlennosti - Fomin, R. N.; Fomina, D. K. (Teorija i Praktika fiziceskoj Kul'tury, 2005)
The purpose of the research was to study the peculiarities of the presynaptic inhibition of the spinal a-motoneuron at the athletes adapted to the motor activity of a different orientation.